Kebijakan Luar Negeri Amerika Serikat Sebagai Manifestasi Politik Domestik: Pengaruh Kelompok Evangelis Terhadap Perdamaian Palestina-Israel - Feizal Reza Pahlevi; Mohamad Rosyidin; Marten Hanura (Journal of International Relations, 2022)
United States (US) established the Middle East as a strategic area in the context of its foreign policy, one of the things is to pursue peace in the Palestinian-Israeli conflict. The US provides Israel takes more benefits in the middle of a peace conflict outcome instead of being a wise peacemaker. The discourse can be proven in US foreign policy in the era of Donald Trump's presidency, the effort for peace in the Palestinian-Israeli conflict is reflected in the controversial policy in the form of a Deal of The Century and Abraham Accord. This study aims to explain how the influence of the Evangelis group as a domestic factor can encourage US foreign policy in favor of Israel in the midst of peace efforts for the Palestinian-Israeli conflict. In this study, the author applies the theory of ideational liberalism which assumes that state preference is shaped by the values and identity of a group that influences foreign policy. Furthermore, the author adopts a qualitative research method with an explanatory type. The results of the study show that the partiality of the US toward Israel in the context of Palestinian-Israeli peace efforts derives from the preference of the Evangelicals group which parts from the belief in Jesus' Second Coming.